Central African Republic Economic Update, July 2021 : Investing in Human Capital to Protect the Future - World Bank (World Bank, Washington, DC, 2021)
The economy of the Central African Republic (CAR) decelerated in 2020 compared to 2019. Despite a relatively contained health impact, the coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on the country’s economy, with the disruption in global value chains, low external demand, and domestic containment measures that significantly affected trade, transport, and tourism. Nevertheless, CAR’s GDP growth of 0.8 percent has outpaced the average of regional peers (−2.9 percent) and countries affected by fragility, conflict and violence (FCV) (−1.7 percent). On the supply side, the positive dynamic of the agriculture sector prevented the economy from entering a recession, and the forestry and telecommunications sectors were more resilient than expected. On the demand side, private consumption contracted in 2020, reflecting a decline in household income owing to the pandemic. As a result, the extreme poverty rate increased from 70.7 percent in 2019 to 71.4 percent, affecting a total of more than 3.4 million people, in 2020. CAR’s current account balance (CAD) deteriorated in 2020. The current account deficit widened from 4.8 percent of GDP in 2019 to 8.7 percent of GDP in 2020, driven by weak external demand and private transfers as well as an increased deficit of the balance on goods. With the COVID-19 pandemic, goods exports declined while non-oil imports were boosted by donor-funded investments. CAR’s current account deficit is not expected to be as severe as that of comparator FCV, CEMAC, and Sub-Saharan African (SSA) countries. The capital account balance improved significantly in 2020 due to the rise in external grants, while the financial account surplus shifted into a deficit. The improvement in the capital account has helped narrow the balance of payments deficit and increasing foreign reserves, which reached a level equivalent to about 3.5 months imports at end-2020.